A critical narrative review of transfer of basic science knowledge in health professions education. Issue 6 (8th February 2018) - Castillo, Jean‐Marie; Park, Yoon Soo; Harris, Ilene; Cheung, Jeffrey J H; Sood, Lonika; Clark, Maureen D; Kulasegaram, Kulamakan; Brydges, Ryan; Norman, Geoffrey; Woods, Nicole
Abstract : Context: 'Transfer' is the application of a previously learned concept to solve a new problem in another context. Transfer is essential for basic science education because, to be valuable, basic science knowledge must be transferred to clinical problem solving. Therefore, better understanding of interventions that enhance the transfer of basic science knowledge to clinical reasoning is essential. This review systematically identifies interventions described in the health professions education (HPE) literature that document the transfer of basic science knowledge to clinical reasoning, and considers teaching and assessment strategies. Methods: A systematic search of the literature was conducted. Articles related to basic science teaching at the undergraduate level in HPE were analysed using a 'transfer out'/'transfer in' conceptual framework. 'Transfer out' refers to the application of knowledge developed in one learning situation to the solving of a new problem. 'Transfer in' refers to the use of previously acquired knowledge to learn from new problems or learning situations. Results: Of 9803 articles initially identified, 627 studies were retrieved for full text evaluation; 15 were included in the literature review. A total of 93% explored 'transfer out' to clinical reasoning and 7% (one article) explored 'transfer in'. Measures of 'transfer out' fostered by basic science knowledge included diagnostic accuracy over time and in new clinical cases. Basic science knowledge supported learning – 'transfer in' – of new related content and ultimately the 'transfer out' to diagnostic reasoning. Successful teaching strategies included the making of connections between basic and clinical sciences, the use of commonsense analogies, and the study of multiple clinical problems in multiple contexts. Performance on recall tests did not reflect the transfer of basic science knowledge to clinical reasoning. Conclusions: Transfer of basic science knowledge to clinical reasoning is an essential component of HPE that requires further development for implementation and scholarship. Abstract : This literature review reveals the positive effect of basic science learning on transfer of knowledge and clinical reasoning.